1981
DOI: 10.1530/jrf.0.0610163
|View full text |Cite
|
Sign up to set email alerts
|

Entry of glycerol into the rat epididymis and its utilization by epididymal spermatozoa

Abstract: The availability of glycerol in the epididymal lumen, and the extent of its utilization by spermatozoa, was studied by measurement of the substrate concentration in epididymal fluid and its oxidation in vitro. The source of luminal glycerol was sought by examining its penetration through the epididymal epithelium of a sperm-free tubule by the technique of luminal perfusion during intravenous infusion of glycerol. [3H]Glycerol was rapidly metabolized to a volatile and mobile molecule that quickly equilibrated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Interestingly, AQP9 is not only permeant to water, but it also allows permeation of neutral solutes such as glycerol (35). Glycerol is accumulated in the lumen of the epididymis (14), and may serve as a metabolic substrate for epididymal sperm. Thus, both the neutral solute permeability and water permeability of AQP9 might represent important functions for the preservation and storage of sperm in the lumen of the epididymis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, AQP9 is not only permeant to water, but it also allows permeation of neutral solutes such as glycerol (35). Glycerol is accumulated in the lumen of the epididymis (14), and may serve as a metabolic substrate for epididymal sperm. Thus, both the neutral solute permeability and water permeability of AQP9 might represent important functions for the preservation and storage of sperm in the lumen of the epididymis.…”
Section: Discussionmentioning
confidence: 99%
“…Significant water reabsorption leading to a marked increase in sperm concentration and luminal hypertonicity occurs in the epididymis (5,(11)(12)(13). In addition, glycerol, a metabolic substrate for epididymal sperm, is accumulated in the lumen of the distal epididymis (14). In the more distal regions of the epididymis and in the vas deferens, water secretion driven by cystic fibrosis transmembrane conductance regulator (CFTR) 2 dependent chloride transport occurs and controls the fluidity of the luminal content (15,16).…”
mentioning
confidence: 99%
“…In the efferent duct of spermiating seabream, we could only consistently detect Aqp10b polypeptides, which were localized in the plasma membrane of the luminal epithelial cells. As suggested for the rat epididymis [74], the expression of the glycerol-transporting Aqp10b paralog in the seabream efferent duct may mediate water transport and provide glycerol as an aerobic metabolic substrate for spermatozoa [75,76]. Representative Western blots of sperm total protein extracts (S-TP; 60 lg) and plasma membrane extracts (PM; 40 lg) of intact sperm (S) and spermatozoa head (H) and flagellum (F) probed with the different aquaporin antibodies as indicated.…”
Section: Aquaporins In Teleost Testis and Spermmentioning
confidence: 97%
“…The presence of glycerol in the rat epididymis and its metabolism by spermatozoa has been reported [75]. In a study of 22 infertile men, sperm AQP7 was nondetectable in five of them who showed slightly lower sperm motility than the other patients [76].…”
Section: Aqp7mentioning
confidence: 98%